Post-transcriptional gene silencing mediated by microRNAs is controlled by nucleoplasmic Sfpq. Issue 1 (December 2017) - Bottini, Silvia; Hamouda-Tekaya, Nedra; Mategot, Raphael; Zaragosi, Laure-Emmanuelle; Audebert, Stephane; Pisano, Sabrina; Grandjean, Valerie; Mauduit, Claire; Benahmed, Mohamed; Barbry, Pascal; Repetto, Emanuela; Trabucchi, Michele
Abstract There is a growing body of evidence about the presence and the activity of the miRISC in the nucleus of mammalian cells. Here, we show by quantitative proteomic analysis that Ago2 interacts with the nucleoplasmic protein Sfpq in an RNA-dependent fashion. By a combination of HITS-CLIP and transcriptomic analyses, we demonstrate that Sfpq directly controls the miRNA targeting of a subset of binding sites by local binding. Sfpq modulates miRNA targeting in both nucleoplasm and cytoplasm, indicating a nucleoplasmic commitment of Sfpq-target mRNAs that globally influences miRNA modes of action. Mechanistically, Sfpq binds to a sizeable set of long 3′UTRs forming aggregates to optimize miRNA positioning/recruitment at selected binding sites, including let-7a binding to Lin28A 3′UTR. Our results extend the miRNA-mediated post-transcriptional gene silencing into the nucleoplasm and indicate that an Sfpq-dependent strategy for controlling miRNA activity takes place in cells, contributing to the complexity of miRNA-dependent gene expression control. MicroRNAs have been best characterized for their functions in the cytoplasm; however, there is growing evidence of a nuclear localized role. Here, the authors identify Sfpq as an Ago2-interacting protein that modulates miRNA activity in both the nucleus and cytoplasm.